Pengetahuan Zakat Dalam Islam Untuk Masyarakat - Dinda Haqie Prasetyo; Talitha Rahma Aulia Santosa; Heri Nur Hadiyanto; Masrurotul Isnan; Putria Eka Hapsari; Dhea Fitria Kurniawati; Ibrahim Aufa; Wafiq Arsyad Hamada; Nur Rofiq (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
One of the pillars of Islam is paying zakat. Zakat is part of the assets we have that we must spend if we have reached the specified conditions. For Muslims who have the means, of course they are obliged to pay zakat, for example when paying zakat fitrah in the month of Ramadan. Zakat will be distributed to people who are entitled to receive it. The existence of the obligation of zakat is stated in the Koran and must be believed by every Muslim. The purpose of zakat is to train our caring attitude towards the people around us, and to become a form of obedience of Muslims to Allah SWT. in fulfilling obligations. In giving zakat we need to be sincere, without expecting anything in return. Because by giving zakat, the blessings we get do not decrease but increase. However, there are still Muslims who are reluctant to contribute to paying zakat due to their lack of awareness of zakat obligations and the wisdom of zakat itself. Therefore, there is a need for further explanation regarding what zakat is, what its benefits are, what the law is in Islam and the wisdom of giving zakat.